CHILDFREE CAMPAIGN PHENOMENON OF HADITH PERSPECTIVE: HADITH ANALYSIS OF MULTIPLYING CHILDREN USING YUSUF QARDHAWI'S HERMENEUTICS (International Conference on Social and Islamic Studies, 2021)
Childfree is an understanding that believes that a family does not need to have children or offspring, Childfree is a lifestyle that refuses to give birth, adopts, or in other words does not want to have children for married couples. Childfree is a common practice for many people, both men and women, whether the choice is forced or self-conscious. The childfree phenomenon raises pros and cons among young people, they use certain arguments to strengthen their arguments. Therefore, this paper discusses the child-free phenomenon from the perspective ofhadith, especially the hadith about multiplying offspring which is interpreted by the hermeneutical perspective of Yusuf al-Qardhawy. This article belongs to the category of qualitative research with the type of library research based on library data, reading, recording and managing research materials. The analytical method used in this study is descriptive analysis with a partial-simultaneous approach in the realm of hadith. The results of the study show that the child-free phenomenon is contrary to the hadith of multiplying offspring, because it contains an invitation not to have children, while the Prophet ordered his followers to marry fertile women in order to have children. Women are equipped with the advantage of "great affection" so that they can educate their children to create "a superior and pious generation".